Мета, предмет і завдання судової медицини - Моїсеєнко, О. С.; Moiseienko, O. S. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 2. - С. 282-288, 2023)
Спираючись на аналіз наукових поглядів учених, запропоновано авторське визначення поняття «судова медицина». Виокремлено мету, предмет і завдання судової медицини. Аргументовано, що судова медицина має на меті забезпечити точність і об’єктивність у визначенні причин та наслідків насильства та інших видів травматичних подій для забезпечення правосуддя і захисту громадянських прав.

It has been established that forensic medicine is a branch of medicine that deals with the application of medical knowledge and methods to resolve legal issues, in particular those related to death, injury and other types of violence. The main purpose of forensic medicine is to examine the bodies of the dead or injured in order to determine the cause of death or injury, as well as to determine the possible criminal element in the act. To do this, forensic physicians use methods of body examination, evidence collection and expert analysis. It has been generalised that forensic medical examination as a subject of forensic medicine is a scientific and practical research carried out by specially trained specialists with the aim of providing an objective assessment of medical issues in cases brought before a court. This examination may include determining the causes and circumstances of death, assessing injuries, determining the severity and possible consequences of injuries, examining the patient's medical history, and other medical issues that may be relevant to the resolution of court cases. The results of a forensic medical examination may be used as evidence in a court of law. It has been stated that the main tasks of forensic medicine as a branch of science are: study of human physiology and pathology, as well as the relationship of these processes with the knowledge of the cause of death and other traumatic injuries; development and improvement of methods for detection and assessment of traumatic injuries and their consequences, as well as establishment of the relationship between trauma and health consequences; detection of the impact of physical and chemical factors on human health, as well as establishment of the causes and consequences of the impact of these factors; determining the state of human health in the context of criminal investigation, including assessment of the state of alcohol or drug intoxication and its impact on human behaviour and actions; studying the relationship between the state of health and the crime committed, as well as establishing the facts of the presence and nature of injuries of victims.

Опираясь на анализ научных взглядов ученых, предложено авторское определение понятия «судебная медицина». Выделены цель, предмет и задачи судебной медицины. Аргументировано, что судебная медицина имеет целью обеспечить точность и объективность в определении причин и последствия насилия и других видов травматических событий для обеспечения правосудия и защиты гражданских прав.
Purpose, subject matter and objectives of forensic medicine
Keywords: судова медицина; судова експертиза; судово-медична експертиза; завдання судової медицини; forensic medicine; forensic examination; forensic medical examination; tasks of forensic medicine; судебная медицина; судебная экспертиза; судебно-медицинская экспертиза; задачи судебной медицины